Analysis Of The Characteristics And Challenges Of The Firefighter Profession In Singaraja Regency - I Nyoman Kariawan; Ni Putu Tirka Widanti; Ida Ayu Putu Sri Widnyani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Abstract The development of urban areas has brought significant challenges, such as the rapid flow of population migration from rural to urban areas and the expansion of various zones, including residential, industrial, and commercial areas. Ironically, this situation also brings its own logical consequences, such as the threat of fire hazards. Based on the background of the issues outlined above, the author formulates the following problem: How can the characteristics and challenges of the firefighting profession in Singaraja Regency be analyzed? The analysis of the characteristics and challenges of the firefighting profession in Singaraja Regency reveals that the firefighting profession entails high risks to the safety of both the firefighters themselves and others. Therefore, to apply for a position as a firefighter, one must possess strong physical abilities and extensive knowledge of disaster management and victim rescue procedures. Keywords: Characteristic, Challengers, Firefighters